The generations theory and the advertising impact on consumer - Popovich, S. V.; Bakina, Tetiana; Бакіна, Тетяна Володимирівна; Бакина, Татьяна Владимировна (Мелітополь: ТДАТУ, 2019)
In any generation, there are certain features of their psychology, certain advantages that affect what choices they make. It is very important to understand and study your target audience, so that your product is relevant, and subsequently became a best seller
Keywords: digital advertising; consumer; generation Z; digital people